STRATEGY TO IMPROVE BUSINESS PERFORMANCE OF PALM OIL SECTOR - Othman, Lie; Heriyanto, Meyzi; Kasmiruddin, Kasmiruddin; Fadli, Mashur; Zulkarnaini, Zulkarnaini; Ikhsan, Masrul (Sosiohumaniora, 2025)
his study aims to analyze the effect of digital marketing, marketing strategy, and knowledge management on improving the performance of the palm oil sector in Merangkai Village, Siak Regency. The research method used is quantitative with a causal design. Primary data was collected through a census technique from the entire population, namely 35 business actors, using a structured questionnaire. The data was then analyzed using Partial Least Square (PLS)-based Structural Equation Modeling (SEM) to test the relationship between variables. The results revealed that marketing strategy had a positive and statistically significant effect on business performance. Conversely, digital marketing and knowledge management were found to have no significant direct effect. The adjusted R-square value of 0.443 indicates that the three independent variables together explain 44.3% of the variation in business performance, while the remaining 55.7% is influenced by factors outside the research model. The implications of these findings indicate that efforts to improve business performance should prioritize the refinement of marketing strategies, particularly in terms of market segmentation, target market determination, and appropriate positioning. Meanwhile, digitalization and knowledge management initiatives require more targeted and contextual intervention designs. Recommendations include capacity building programs for digital literacy, integration of local wisdom into business strategies, and continuous evaluation to ensure marketing effectiveness..